2015
DOI: 10.4314/ajtcam.v12i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Bio-activities and phytochemical investigation of <i>Cnestis palala</i> (Lour.) Merr.

Abstract: Background: In traditional medicines, the root of Cnestis palala was used for the treatment of stomach ache, malaria, urinary track disorders and snakebite. The seed was used for poisoning rat and stray dogs. However, the bioactivities and chemical constituents have not been reported. So, this will be the first report. Results:The results showed that the ethanol leaf and bark extracts were active against S. aureus and S. epidermidis. The hexane leaf and seed extracts and petroleum ether bark and root extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Merr. (Connaraceae), which has been tested on Staphylococcus aureus and S. epidermidis with MIC value at 500 μg mL − 1 (2.41 mM) against both microorganisms (Dej-adisai et al, 2015). Secondly, viarumacid A, a glucosylated caffeoylquinic acid derivative isolated from S. viarum has been showed to display antioxidant activity (Wu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Merr. (Connaraceae), which has been tested on Staphylococcus aureus and S. epidermidis with MIC value at 500 μg mL − 1 (2.41 mM) against both microorganisms (Dej-adisai et al, 2015). Secondly, viarumacid A, a glucosylated caffeoylquinic acid derivative isolated from S. viarum has been showed to display antioxidant activity (Wu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The result of research by Tanjung et al (2014) indicated that genus of Bauhinia has high antioxidant activity. The results suggested that Cnestis palala is a great potential source of anti-microbial agents (Adisai et al 2015). Cnestis palala and Cnestis sp are species that are originated from the same genus, but they have different color of the wood, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The decoction and infusion of these plants and fungi mixture were traditionally consumed by Jakun women for post-partum recovery and boosting energy. The above-mentioned plants have shown high quantity of bioactive compounds with promising antioxidants acitivities ( Chua et al, 2012 , Dej-adisai et al, 2015 , Lar, 2014 ).…”
Section: Introductionmentioning
confidence: 99%